Enhanced Optical Properties of Ce-Doped ZnO Nanoparticles via A Green Plant-Based Synthesis Approach - Simatupang, Mediniah Putri; Ari Sulistyo Rini; Erwin (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
This study investigated the optical properties of Ce-doped ZnO nanoparticles (Ce/ZnO), synthesized using Pandanus ammaryllifolius leaf extract via a green biosynthesis method. Ce doping concentrations of 1%, 2%, and 3% were applied, and the nanoparticles were annealed at 400 °C for two hours. UV-Vis analysis showed a redshift in the annealed samples, with the wavelength increasing from 368 nm to 370 nm, likely due to particle growth after thermal treatment. In contrast, the unannealed samples exhibited a blueshift, with the maximum absorbance wavelength decreasing from 361 nm to 356 nm. The absorbance values were higher in the annealed samples than in the unannealed ones. The band gap energy of doped ZnO samples decreased slightly after annealing, from 3.20–3.22 eV to 3.15–3.19 eV, indicating improved optical properties. FTIR analysis revealed the presence of Ce–O bonds and functional groups, such as O–H and C–H, with sharper peaks in the annealed samples. The novelty of this study lies in utilizing Pandanus ammaryllifolius leaf extract as a natural reducing and stabilizing agent, providing a sustainable and eco-friendly alternative to conventional chemical synthesis methods. The findings suggest that Ce doping enhances the optical properties of ZnO nanoparticles, making them suitable for specific applications in environmental remediation, such as the degradation of organic pollutants, and in technological fields like photocatalytic devices and UV-absorbing materials.